2011
DOI: 10.1111/j.1439-0272.2011.01167.x
|View full text |Cite
|
Sign up to set email alerts
|

Low inhibin B levels alone are not a reliable marker of dysfunctional spermatogenesis in childhood cancer survivors

Abstract: Hormone and semen analyses were carried out to examine the diagnostic value of hormones and hormone combinations as markers of spermatogenesis in male patients who had received oncological treatment in childhood. Hormone analyses from 73 participants and spermiograms from 42 participants were evaluated. Spearman's correlation coefficients and measures of diagnostic accuracy were calculated for the hormone and semen analysis values. Inhibin B levels of <80 ml/ml, follicle-stimulating hormone (FSH) levels of >10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…The application of inclusion and exclusion criteria to the studies found in the literature yielded four sources of FSH and semen concentration in CCS (Table 1, S2 Table, Fig 1) [5, 14, 32, 33]. Studies identified for full-text analysis, but excluded are listed in S1 References together with reasons for exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…The application of inclusion and exclusion criteria to the studies found in the literature yielded four sources of FSH and semen concentration in CCS (Table 1, S2 Table, Fig 1) [5, 14, 32, 33]. Studies identified for full-text analysis, but excluded are listed in S1 References together with reasons for exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of 25 males, it was found that in prepubertal boys, inhibin B concentration, together with sensitive measurements of FSH concentration, was a potential marker of the gonadotoxic effects of chemotherapy, but not as good as the gold standard (semen analysis) [36]. Two other studies that investigated the diagnostic value of inhibin B concentrations and FSH concentrations for detecting azoospermia and oligospermia showed that measurements of FSH, inhibin B concentrations and using the inhibin-FSH ratio all show fairly diagnostic value for detecting azoospermia [37, 38]. The accuracy of FSH as a predictor of azoospermia in adult survivors of childhood cancer remains controversial, with conflicting results in the published literature.…”
Section: Primary Gonadal Failure In Male Ccs (Table 1)mentioning
confidence: 99%
“…There is also the question of whether hormones are appropriate or sufficiently sensitive to detect a treatment‐induced effect on spermatogenesis. The hypothesis that FSH and inhibin B are good markers of spermatogenesis (Meachem et al, ; Kumanov et al, ) is not universally supported in the literature, and many acute treatment‐induced changes appear the most problematic for a hormone response (Kolb et al, ; Salenave et al, ; Rendtorff et al, ); Small sample sizes and high variability . The human studies sometimes included fewer than 20 men per dose group, which was likely insufficient to identify statistically significant changes in measures with high variability such as semen analysis endpoints.…”
Section: Discussionmentioning
confidence: 99%